Avaliação das indicações da flebotomia terapêutica em pacientes atendidos pelo Hemovida Serviços de Hemoterapia LTDA - Batista, Sabrynna de Oliveira (2018)
The therapeutic phlebotomy is a simple and safe procedure in which blood is withdrawn from the patient and is aimed at relieving symptoms due to the excess or accumulation of blood in parenchymal organs, as well as the decrease of blood viscosity caused by some pathologies. This procedure has as main indications diseases such as hereditary hemochromatosis, polycythemia vera, polyglobulia, and other conditions that increase the hematocrit (PCV) of the individual or cause iron overload. The aim of this study was to conduct a qualitative and quantitative study of the main clinical indications of patients who underwent therapeutic phlebotomy at the Hemovida blood bank from January 2014 to December 2017. Were analyzed the records of 322 patients who underwent therapeutic phlebotomy, with hemochromatosis being the most prevalent indication (75.1%), followed by high ferritin (22.7%) and other indications (2.2%). The majority of the patients who underwent the therapeutic procedure were aged between 50 and 69 years (62,1%) and were male (86.6%). During the period analyzed in this study, 322 patients performed a total of 1,025 bleeds, thus distributed: 68 (21.1%) of the patients performed the procedure once, 104 (32.2%) performed twice, 43 (13%) Three times, 37 (11.4%) four times, 27 (8.3%) performed five times, 18 (5.5%) performed sixe times, 6 (1.8%) seven times , 8 (2.4%) eight times, and 11 (3.4%) did more than nine phlebotomies. Thus, it was concluded that the profile of patients submitted to therapeutic phlebotomy in the Hemovida blood bank during the study period was composed mainly of men older than 50 years of age and that the most prevalent indication for treatment was hemochromatosis.